Association between Disease Activity and Depression inRheumatoid Arthritis Patients - Mudjaddid, E; Puspitasari, Myra; Setyohadi, Bambang (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Rheumatoid Arthritis (RA) is a chronic, systemic disease that cause synovialinflammation and progressive destruction to cartilages and deformities. Prevalence of depressionin RA patients is 20 to 30%. Disease activity is considered to have association with depression. This study aims to identify the prevalence of depression in RA patients and the associationbetween disease activity index and depression in RA patients. Methods. A cross-sectional study of 145 RA patients that fulfilled the inclusion criteria was conducted in Rheumatology Outpatient Clinic at Cipto Mangunkusumo Hospital Jakarta from January to March 2017.Evaluation of Disease Activity Score - 28 (DAS 28) and Back Depression Inventory (BDI) was done to the patients. Statistical analysis was performed using SPSS version 20. Categorical variables were compared using chi-square test. Results. A total of 145 subjects were included in this study and most of them were female (90.3%). Median age of subjects was 55 years (range 19-83 years). Forty five subject (31%) were identified having psychosocial stressor. The proportion of depression in RA patients was 35.9% (95% CI 30-42%). Based on Disease Severity Score, it was found that subject with mild, moderate, and severe score were 24 (82.8%), 52 (66.7%), and 4 (23.5%), respectively. There was significant association between disease activity with depressionin rheumatoid arthritis patient (p= 0.001).